2013
DOI: 10.1128/jb.00171-13
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Opa-Expressing and Opa-Deficient Neisseria gonorrhoeae Strains Differentially Stimulate and Survive Exposure to Human Neutrophils

Abstract: The Neisseria gonorrhoeae (the gonococcus [Gc]) opacity-associated (Opa) proteins mediate bacterial binding and internalization by human epithelial cells and neutrophils (polymorphonuclear leukocytes [PMNs]). Investigating the contribution of Opa proteins to gonococcal pathogenesis is complicated by high-frequency phase variation of the opa genes. We therefore engineered a derivative of Gc strain FA1090 in which all opa genes were deleted in frame, termed Opaless. Opaless Gc remained uniformly Opa negative (Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
143
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(164 citation statements)
references
References 65 publications
13
143
1
Order By: Relevance
“…NET integrity was comparable between parent and Δnuc N. gonorrhoeae at times up to 1 hour, after which it decreased with parent N. gonorrhoeae but increased in Δnuc-exposed cells (Figure 2). Consistent with previous findings for this opa-deficient background [18], neither Nuc-containing nor Δnuc N. gonorrhoeae induced production of reactive oxygen species by neutrophils (Supplementary Figure 1C), indicating that effects on NET integrity were not due to differences in the neutrophil oxidative burst. Together, these results show N. gonorrhoeae induces rapid formation of NETs by human neutrophils and that NET integrity decreases over time with Nuc-containing N. gonorrhoeae.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…NET integrity was comparable between parent and Δnuc N. gonorrhoeae at times up to 1 hour, after which it decreased with parent N. gonorrhoeae but increased in Δnuc-exposed cells (Figure 2). Consistent with previous findings for this opa-deficient background [18], neither Nuc-containing nor Δnuc N. gonorrhoeae induced production of reactive oxygen species by neutrophils (Supplementary Figure 1C), indicating that effects on NET integrity were not due to differences in the neutrophil oxidative burst. Together, these results show N. gonorrhoeae induces rapid formation of NETs by human neutrophils and that NET integrity decreases over time with Nuc-containing N. gonorrhoeae.…”
Section: Resultssupporting
confidence: 80%
“…Piliated, opacity protein-deficient N. gonorrhoeae (strain FA1090) was used for most experiments [18]. An insertiondeletion mutation with a kanamycin resistance cassette was generated in nuc (NGO0969), using plasmid pCTS#43 [17].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Characterization of individual CEACAM function in neutrophilic cell lines showed that Opa-mediated neutrophil activation is mediated by CEACAM3 signaling, while CEACAM1 and CEACAM6 allowed bacterial internalization without triggering production of reactive oxygen species (ROS) or release of toxic granule proteins (44). However, all of the studies focusing on neutrophil responses to Opa-CEACAM binding have been done exclusively with the commonly studied N. gonorrhoeae strains MS11 (44,45,47,61,62) and FA1090 (63,64).…”
Section: Resultsmentioning
confidence: 99%
“…Gonococcal opacity (Opa) proteins, which are subject to phase variation, have been shown to differentially affect gonococcal survival in association with neutrophils (16). Therefore, all neutrophil experiments were conducted in the FA1090 Opa-deficient (Opaless) background (43). Primary human neutrophils seeded onto chambered cover glasses and induced to form NETs with phorbol myristate acetate (PMA) (53) were stained with antibodies against CP and gonococci.…”
Section: Tdfh and Tdfj Production Is Zn Repressed And Zur Regulatedmentioning
confidence: 99%